Bacteriology of infected burn wounds in hospitals in and around Davangere - S. Goutham Patil; R Eshwar Singh (Tropical Journal of Pathology and Microbiology, 1970)
Introduction: Study was conducted to isolate and identify the aerobic bacterial flora in burn wound patients admitted in and around hospitals of Davanagere. It also includes knowing common microbial pathogen involved in causing infection & antibiotic resistance pattern of isolates.Methods: The study was done on 100 patients admitted to burns wards in the following 2 Hospitals in Davangere: Chigateri Government Hospital and Bapuji Hospital. Sample is collected from patients in 2 different swabs, one for smear and another for culture. Each pair of swabs from single patient is analysed for 3 days of thorough investigations like Day 1: Examining sample under Gram’s stain and inoculating for sample for culture. Day 2: Noting the morphological characteristics of growth and further for microscopy. Day 3: Final identification of organism and biochemical tests for gram negative organisms.Result: According to the study results have been following in different categories like: Most common organisms found: Staphylococcus aureus and Pseudomonas aeruginosa. Staphylococcus aureus is most resistant to Penicillin G and 60% resistant to Methicillin whereas it is most sensitive to Chloramphenicol. It has various pattern of sensitivity for others various antibiotics.Conclusion: As we get results from the study, it can concluded that staphylococcus aureus and Pseudomonas aeroginosa are the most common organisms causing infections in burn patients, and these organisms are becoming resistant to most of the present day antibiotics like Penicillin G and Methicillin, treating resistant strains is the challenging job now a days.